Penerapan New Public Service (NPS) dalam Pelayanan Identitas Kependudukan Digital (IKD) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tangerang - Trisya Walza Rizkita; Rifdah Silawarti; Bagus Sajiwa; Muhamad Rizqi Priatna; Irvan Arif Kurniawan (Public Service and Governance Journal, 2025)
In response to the major impact of rapid developments in the era of globalization on the public service paradigm, many government institutions have implemented the New Public Service (NPS) concept. This concept is community-oriented and prioritizes the principle of innovation to create more efficient and responsive public services. To understand and analyze the implementation of the New Public Service (NPS) in Digital Population Identity (IKD) services at the Tangerang Regency Dukcapil Office, this research uses a qualitative approach with descriptive methods and is based on the seven NPS principles initiated by Denhardt J.V & Denhardt R.B (2003). The research informants came from the Population Administration Information Systems Section. Data collection techniques are carried out through interviews, observation and documentation. The implementation of the New Public Service (NPS) in the Tangerang Regency Dukcapil Disdukcapil in IKD services has generally illustrated an effort to create a better public service environment, sensitive to community needs, and respecting the rights of citizens. However, the research results show that there is still one principle that has not been implemented, namely "Value people, not just productivity." Therefore, to maximize results, continuous efforts are needed to increase public awareness, provide adequate resources, and utilize the latest information technology in public services.